INNOVATION AS AN IMPORTANT FACTOR IN THE INTENSIFICATION OF AGRICULTURE (THE EXAMPLE OF REPABLIC OF ARMENIA) - S. Petrosyan; A. Palikyan (Вестник университета, 2019)
It is know that the increase of agricultural production efficiency is achieved mainly due to the intensification of innovation activities. In the article by the authors are substantiate the importance and necessity of innovation activities in the development of agriculture of the Republic of Armenia and based on the analysis made a number of suggestions for the improvement of the innovation process in the sphere.